How to keep it adequate: A protocol for ensuring validity in agent-based simulation. (January 2023) - Troost, Christian; Huber, Robert; Bell, Andrew R.; van Delden, Hedwig; Filatova, Tatiana; Le, Quang Bao; Lippe, Melvin; Niamir, Leila; Polhill, J. Gareth; Sun, Zhanli; Berger, Thomas
Abstract: There has so far been no shared understanding of validity in agent-based simulation. We here conceptualise validation as systematically substantiating the premises on which conclusions from simulation analysis for a particular modelling context are built. Given such a systematic perspective, validity of agent-based models cannot be ensured if validation is merely understood as an isolated step in the modelling process. Rather, valid conclusions from simulation analysis require context-adequate method choices at all steps of the simulation analysis including model construction, model and parameter inference, uncertainty analysis and simulation. We present a twelve-step protocol to highlight the (often hidden) premises for methodological choices and their link to the modelling context. It is designed to aid modelers in understanding their context and in choosing and documenting context-adequate and mutually consistent methods throughout the modelling process. Its purpose is to assist reviewers and the community as a whole in assessing and discussing context-adequacy. Graphical abstract: Image 1 Highlights: A comprehensive understanding of validation for agent-based models and beyond. 11 dimensions to characterise the modelling context and purpose. A characterisation of the premises of common validation approaches. A detailed protocol to guide context-adequate model construction and review. A consistent tracking of uncertainty propagation through the modelling process.